1519. Management and Outcomes of Children with Extended-Spectrum Cephalosporin-Resistant Urinary Tract Infections (ESC-R UTIs). (26th November 2018) - Wang, Marie; Greenhow, Tara; Lee, Vivian; Beck, Jimmy; Bendel-Stenzel, Michael; Hames, Nicole; McDaniel, Corrie; King, Erin; Sherry, Whitney; Parmar, Deepika; Patrizi, Sara; Srinivas, Nivedita; et al.
Abstract: Background: ESC-R UTIs often have limited oral antibiotic options with some children receiving a course of intravenous (IV) antibiotics. Our objectives were to determine predictors of long course IV therapy and the association between short-course therapy and UTI relapse. Methods: We conducted a multicenter retrospective cohort study of children < 18 years with ESC-R UTIs presenting to an acute care setting of 5 children's hospitals and a large managed care organization from 2012 to 2017. ESC-R UTI was defined as having a urinalysis with positive leukocyte esterase or >5 white cells per high power field and urine culture with ≥50, 000 colony-forming units per milliliter of E. coli or Klebsiella spp. nonsusceptible to ceftriaxone. Children with urologic surgery, immunosuppression and nonrenal chronic conditions were excluded. Long course therapy was defined as ≥5 days and short course as 0–4 days of a concordant IV antibiotic (an agent to which the isolate was susceptible). Relapse was defined as UTI with the same organism within 30 days. Limited oral antibiotic options were defined as nonsusceptibility to amoxicillin–clavulanate, ciprofloxacin, and trimethoprim–sulfamethoxazole. Predictors of long course therapy were determined using mixed effects logistic regression with hospital site as a random effect. Since UTI relapse was a rare outcome, we evaluated the association between short-course therapy and UTI relapse using Fisher's exact test. Results: Of 383 children with ESC-R UTIs, 80% were female, median age was 3 years (interquartile range 0.7–7.8), and 24% had a prior UTI. Forty-five children (12%) received long course therapy and 338 (87%) received short-course therapy. Predictors of long course therapy included age < 2 months (adjusted odds ratio [AOR] 61.4, 95% confidence interval [CI] 12.5–302), male sex (AOR 3.0, 95% CI 1.2–7.8), and limited oral antibiotic options (AOR 5.3, 95% CI 2.2–12.6). UTI relapse occurred in 1/45 (2%) children treated with long course therapy and in 3/335 (0.9%) treated with short-course therapy ( P = 0.40). Conclusion: Long course IV therapy in children with ESC-R UTIs was more likely in infants < 2 months, males and those with limited oral antibiotic options. UTI relapse was rare and not associated with short course/no IV therapy. Disclosures: All authors: No reported disclosures.